Willingness to Pay for Improved Solid Waste Management in Itahari, Sunsari, Nepal - Khadka, Umesh (Economic Journal of Nepal, 2023)
Solid waste management (SWM) is a widespread problem in urban areas of developed and underdeveloped countries. Unplanned urbanization, rapid population growth, and migration of people from rural to urban areas are the leading causes for the problem of SWM in the major cities of Nepal. Inadequate services for solid waste collection can lead to environmental problems, pollution, health risks, and economic burdens for the society. Understanding the willingness to pay (WTP) of residents for improved solid waste collection is crucial for deciding effective pricing policies and waste collection techniques. In this context, the main aim of the study is to examine the WTP for the services of improved SWM in the study area. Using simple random sampling method, 377 households were taken as a sample to estimate the WTP for SWM through the Contingent Valuation Model (CVM) and Tobit regression. A field survey was conducted to collect the required data and information related to the WTP of households through the structured questionnaire. The study found that 83.55 percent of respondents would pay for improved SWM services, and the willingness to pay varies from NRs. 50 to NRs.500 per month. Tobit regression results identified the factors influencing WTP for improved SWM in the study area. The factors of gender, ownership of the house, education, profession, income level, and service satisfaction are statistically significant in determining the WTP for SWM.